LONGEVITY BEHAVIORS IN OLDER AFRICAN AMERICAN MEN. (11th November 2018) - Locks, S; Waters, C
Abstract: In general, Americans are living longer. African American (AA) men, however have the shortest life expectancy. Yet, clear reasons for this disparity and counter mechanisms are unknown. Health behaviors are believed to enhance longevity, but studies about the health behaviors of older AA men is sparse. The purpose of this qualitative study was to explore the health behaviors and lived experiences of older AA men in regard to longevity. Using a semi-structured interview guide, face-to-face interviews and participant observations were conducted with a purposive sample of six community-dwelling AA men, 70 years and older. Participants in this pilot study were recruited from a predominantly AA census tract in northern California using fliers posted and announcements made at senior centers and local churches, along with snowballing techniques. The interviews lasted 1–2 hours and were audio recorded and transcribed verbatim. Using an iterative, inductive data analytic approach, transcribed documents were coded line by line into categories and then themes. Participant observations were guided by Bortz's principles for living long: daily physical exercise, intellectual activities and social interactions. Codes generate were fatalism, genetics, chronic illnesses, responsibility, beliefs, comparisons, and discrimination. Two major themes evolved: the continuum of health and illness, and surviving a life course in the context of cultural meaning. Findings suggest greater attention needs to be given to understanding the culturally-specific health practices and chronic illness management of older AA men in order to maintain health and achieve a full life in terms of quality and longevity.